Condensed and Incomplete Legal Practice of Time - Tatiana Mihailovna Fakhrutdinova (Сибирское юридическое обозрение, 2011)
This article is about the working time and its raneties. This a scientific publication analyzes the problem of establishing a part-time and reduced working time. Based on an analysis of Russian legislation in the workplace, the author formulates the criteria to distinguish these kinds of working time.